2014
DOI: 10.1093/brain/awu061
|View full text |Cite
|
Sign up to set email alerts
|

Working memory network plasticity after anterior temporal lobe resection: a longitudinal functional magnetic resonance imaging study

Abstract: Temporal lobe surgery can control seizures in drug-resistant epilepsy, but its impact on working memory is poorly understood. Using functional MRI, Stretton et al. reveal improvements in working memory post-surgery, which depend upon the functional capacity of the hippocampal remnant and the functional reserve of the contralateral hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…The lack of clear lateralization in amygdala reactivity to faces does not rule out the possibility that the left and right amygdala can modulate core face processing areas differently, an idea that would fit the present observation. The observed group differences are also in line with a previous fMRI study on working memory in patients with ATR, which also found different activation patterns in left and right resected patients (Stretton et al, 2014). The more widespread reductions in neural reactivity in patients with right ATR did however not correspond to behavior, because the accuracy in face matching did not differ between patients with right and left sided resection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The lack of clear lateralization in amygdala reactivity to faces does not rule out the possibility that the left and right amygdala can modulate core face processing areas differently, an idea that would fit the present observation. The observed group differences are also in line with a previous fMRI study on working memory in patients with ATR, which also found different activation patterns in left and right resected patients (Stretton et al, 2014). The more widespread reductions in neural reactivity in patients with right ATR did however not correspond to behavior, because the accuracy in face matching did not differ between patients with right and left sided resection.…”
Section: Discussionsupporting
confidence: 89%
“…As in our ROI-analysis, the reductions in the right resected group were more widespread than in the left resected group. Previous neuroimaging studies of face processing have also found activations in the superior parietal cortex (Stretton et al, 2014), motor areas (Kilts, Egan, Gideon, Ely, & Hoffman, 2003) and the striatum (Fusar-Poli et al, 2009). Our findings suggest that face-related activity in these areas is modulated by the MTL.…”
Section: Discussionmentioning
confidence: 93%
“…According to this concept, regions or circuits within the brain are able to counteract and/or counterbalance age-related alterations or disease pathologies by reorganizing synaptic structure, connections, and ultimately function via a multitude of molecular and cellular pathways (Honer et al, 2012). A primary example of this form of neuroplasticity is found in the hippocampus, a major component of the limbic system that displays neural reorganization after brain injury in animal models of neural damage and in human neurological diseases including epilepsy (Stretton et al, 2014) and AD (DeKosky et al, 2002; Davis et al, 1999). Therefore, the overall goal of this review is to present evidence derived from clinical pathological investigations that the hippocampus, a component of the medial temporal lobe (MTL) memory circuit, displays cellular and structural alterations indicative of neural plasticity during the progression of AD.…”
mentioning
confidence: 99%
“…However, the benefit of epilepsy surgery must be weighed against the risk of cognitive decline, which is commonly observed in the domains of language and long‐term memory . Conversely, postsurgical gains in executive domains such as attention and working memory can be observed . Clinical (e.g., epilepsy duration, presurgical cognitive level) and demographic (e.g., age) factors predict postsurgical cognitive outcomes .…”
mentioning
confidence: 99%